2018
DOI: 10.1007/s00401-018-1882-3
|View full text |Cite
|
Sign up to set email alerts
|

FGFR1:TACC1 fusion is a frequent event in molecularly defined extraventricular neurocytoma

Abstract: Extraventricular neurocytoma (EVN) is a rare primary brain tumor occurring in brain parenchyma outside the ventricular system. Histopathological characteristics resemble those of central neurocytoma but exhibit a wider morphologic spectrum. Accurate diagnosis of these histologically heterogeneous tumors is often challenging because of the overlapping morphological features and the lack of defining molecular markers. Here, we explored the molecular landscape of 40 tumors diagnosed histologically as EVN by inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
70
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 29 publications
2
70
0
Order By: Relevance
“…In the absence of elevated proliferative rate/mitotic activity, and particularly after complete resection, the rate of recurrence is low [25,41]. While definitive grading criteria have yet to be established and survival data studied in additional independent cohorts, EVN corresponds histologically to WHO grade II, which is in keeping with reported survival data in molecularly-defined EVN, including those bearing FGFR1-TACC1 fusions [67].…”
Section: Fgfr1-tacc1 Fusion In Extra Ventricular Neurocytomasupporting
confidence: 66%
See 1 more Smart Citation
“…In the absence of elevated proliferative rate/mitotic activity, and particularly after complete resection, the rate of recurrence is low [25,41]. While definitive grading criteria have yet to be established and survival data studied in additional independent cohorts, EVN corresponds histologically to WHO grade II, which is in keeping with reported survival data in molecularly-defined EVN, including those bearing FGFR1-TACC1 fusions [67].…”
Section: Fgfr1-tacc1 Fusion In Extra Ventricular Neurocytomasupporting
confidence: 66%
“…DNA methylation-based analysis of a cohort of EVN found that while a subset of histologically diagnosed EVN could be regrouped with other defined, established entities, a large fraction formed a clearly distinct, separate epigenetic group. Importantly, copy number analysis and RNA sequencing demonstrated FGFR1-TACC1 fusion as a recurrent feature within the EVN methylation group (60%), in addition to a small number of other FGFR rearrangements (FGFR3-TACC3, FGFR1-EVI5) [67].…”
Section: Fgfr1-tacc1 Fusion In Extra Ventricular Neurocytomamentioning
confidence: 99%
“…A graphical summary of the evolution of the field within the context of brain tumours is displayed in Figure . DNA methylation is further gaining importance for tumour entity definition and is increasingly being used for the allocation of rare cancers into either known tumour classes or the identification of new entities , a collection of which are summarized in Figure .…”
Section: Dna Methylation In Cancermentioning
confidence: 99%
“…Among paediatric low‐grade gliomas and glioneuronal tumours, at least nine main DNA methylation classes have so far been established and seem sufficiently distinct for tumour classification . The molecular classes are clearly related to the established histological tumour classes although there is typically some degree of reallocation when molecular classes are overlaid on histological series . Figure lists the main molecular classes.…”
Section: Methylation Profiling Of Established Paediatric Brain Tumourmentioning
confidence: 99%
“…In tumours, TACC1 expression significantly associates with lymph node metastasis and poor prognosis (Ding et al , ; Lv et al , ). A FGFR1‐TACC1 fusion capable of constitutive tyrosine kinase activation was found in extraventricular neurocytoma and glioblastoma (Lasorella, Sanson, & Iavarone, ; Sievers et al , ). However, the role of TACC1 has not been described in leukaemia so far.…”
mentioning
confidence: 99%